ALAM SEMESTA (LINGKUNGAN) DAN KEHIDUPAN DALAM PERSPEKTIF BUDHISME NICHIREN DAISHONIN - Sri Rahayu Wilujeng (Universitas Diponegoro, 2014)
Abstract Buddhism taught by Sidhartha Gautama in India about two thousand years B.C. has spread throughout the world. From India to Tibetan Buddhism evolved, China and into Japan. Buddhism in Japan has distinct characteristics compared to Buddhism elsewhere. In Japan, Buddhism is mixed with a strong Japanese spirituality. This paper is the result of a brief research on the book, as well as the Buddhists by means of dialogue. The general objective of this paper is to get a general idea of the concept of Nichiren cosmology, particularly on the subject of the universe (environment) and life. The specific objective of this paper is the growing awareness to be open to understand other religions. It takes an attitude to want to investigate a religion without fanaticial attitude or prejudice. Key words: Nichiren Daishonin, Universe, Life